104k views
3 votes
Use factoring to solve the equation for x: (x−2)(2x−3)=(x−2)(x+1).

User Zserge
by
5.3k points

1 Answer

2 votes

Answer:

x = 4, 2

Explanation:


(x-2)(2x-3)=(x-2)(x+1)


\\\Rightarrow 2x^2-7x+6=x^2+x-2x-2\\\Rightarrow 2x^2-7x+6-x^2+x-2x-2=0\\\Rightarrow x^2-6x+8=0

While splitting the middle term the sum of the term should give us the middle term and their product should give the last term


\\\Rightarrow x^2-4x-2x+8=0

-4-2 = -6


-4* -2=8


\\\Rightarrow (x-4)(x-2)=0\\\Rightarrow x=4, 2

Hence, x = 4, 2

User Kamal Joshi
by
5.1k points